THE INFLUENCE OF SOCIAL MEDIA ON PUKIS CAKE CONSUMPTION TRENDS AMONG MILLENIALS AND GEN Z: A QUESTIONNAIRE-BASED STUDY - Fauziah, Ade Ahmal; Nisa, Aqila Ulya; Vinawati, Lisna Nur; Yunita, Vera; Prastyo, Yudi (Journal of Information Systems Management and Digital Business, 2025)
Social media is a digital platform that allows users to communicate, share information, and interact in various forms, such as text, images, videos, and audio. Social media allows real-time interaction and builds social networks without geographical limitations. Social media has become a major factor in shaping consumption trends among millennials and Gen Z, including in the culinary industry. In the business world, trends are very important because they can help companies understand consumer behavior and adjust marketing strategies to stay relevant to the market. This study aims to analyze the influence of social media on pukis cake consumption trends among this generation. The research method used is a quantitative approach with a survey technique through a questionnaire distributed to respondents who actively use social media. In addition, interviews with pukis cake business actors were also conducted to understand the digital marketing strategies implemented. The results of the study show that exposure to culinary content on social media, such as reviews, photos, and videos, has a significant effect on pukis cake consumption decisions. Platforms such as Instagram, TikTok, and Facebook have become the main media in promoting products, where aesthetic factors, customer testimonials, and influencer marketing strategies play an important role. In addition, easy access to information about sales locations and online ordering also increases consumer purchasing interest. Thus, it can be concluded that social media has a major impact in shaping the trend of pukis cake consumption among millennials and Gen Z. The implications of this study emphasize the importance of utilizing social media as a marketing strategy for pukis cake entrepreneurs to increase competitiveness and reach a wider market. The level of respondent satisfaction with the choice of pukis cakes currently available is around 45%.